Shareholder democracy in play: Career consequences of proxy contests - Fos, Vyacheslav; Tsoutsoura, Margarita (Journal of Financial Economics, 2014)
This paper shows that proxy contests have a significant adverse effect on careers of incumbent directors. Following a proxy contest, directors experience a significant decline in the number of directorships not only in the targeted company, but also in other nontargeted companies. The results are established using the universe of all proxy contests during 1996–2010. To isolate the effect of the proxy contest, our empirical strategy uses within-firm variation in directors׳ exposure to the possibility of being voted out and exploits the predetermined schedule of staggered boards that allows only a fraction of directors to be nominated for election every year. We find that nominated directors relative to non-nominated ones lose 58% more seats on other boards. The evidence suggests the proxy-contest mechanism imposes a significant career cost on incumbent directors.